Testing violation of the Leggett–Garg-type inequality in neutrino oscillations of the Daya Bay experiment - Qiang Fu; Xurong Chen (European Physical Journal C: Particles and Fields, 2017)
Abstract The Leggett–Garg inequality (LGI), derived under the assumption of realism, acts as the temporal Bell inequality. It is studied in electromagnetic and strong interaction like photonics, superconducting qubits and nuclear spin. The weak interaction two-state oscillations of neutrinos affirmed the violation of Leggett–Garg-type inequalities (LGtI). We make an empirical test for the deviation of experimental results with the classical limits by analyzing the survival probability data of reactor neutrinos at a distinct range of baseline dividing energies, as an analog to a single neutrino detected at different times. A study of the updated data of the Daya Bay experiment unambiguously depicts an obvious cluster of data over the classical bound of LGtI and shows a $$6.1σ $$ 6.1 σ significance of the violation of them.